Electrostatic flocking of salt-treated microfibers and nanofiber yarns for regenerative engineering - Alec McCarthy (Elsevier, 2021)
Electrostatic flocking is a textile technology that employs a Coulombic driving force to launch short fibers from a charging source towards an adhesive-covered substrate, resulting in a dense array of aligned fibers perpendicular to the substrate. However, electrostatic flocking of insulative polymeric fibers remains a challenge due to their insufficient charge accumulation. We report a facile method to flock electrostatically insulative poly(ε-caprolactone) (PCL) microfibers (MFs) and electrospun PCL nanofiber yarns (NFYs) by incorporating NaCl during pre-flock processing. Both MF and NFY were evaluated for flock functionality, mechanical properties, and biological responses. To demonstrate this platform's diverse applications, standalone flocked NFY and MF scaffolds were synthesized and evaluated as scaffold for cell growth. Employing the same methodology, scaffolds made from poly(glycolide-co-l-lactide) (PGLA) (90:10) MFs were evaluated for their wound healing capacity in a diabetic mouse model. Further, a flock-reinforced polydimethylsiloxane (PDMS) disc was fabricated to create an anisotropic artificial vertebral disc (AVD) replacement potentially used as a treatment for lumbar degenerative disc disease. Overall, a salt-based flocking method is described with MFs and NFYs, with wound healing and AVD repair applications presented.